EFL Students’ Perceptions of Their Metacognitive Awareness in English Language Learning - Putri, Natalia Destiana; Kuswandono, Paulus; Ena, Ouda Teda (Pioneer: Journal of Language and Literature, 2024)
Effective English language teaching demands proficient teachers, as pre-service teachers in the English Education department must possess strong English proficiency to teach effectively. This study investigates the perceptions of metacognitive awareness among pre-service EFL teachers in an Indonesian context. Quantitative data were collected using Balcikanli’s Metacognitive Awareness Inventory (MAI), and qualitative data were gathered through semi-structured interviews. The findings reveal that pre-service teachers in the English Language Education department display varying levels of metacognitive awareness, which impacts their ability to effectively teach English. 60% of participants have a moderate perception of their metacognitive awareness, while 40% exhibit a high level. Key aspects of metacognition, including declarative, procedural, and conditional knowledge, as well as regulation of cognition through planning, monitoring, and evaluating, were examined. It highlighted that the pre-service teachers are generally aware of their learning strengths and weaknesses but face challenges in regulating learning effectively. The study contributes to the field of English language learning and teaching by emphasizing the role of metacognitive awareness in achieving successful language acquisition and suggests that ongoing support and training are essential for pre-service teachers to become effective educators.